PENGARUH PENERAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP CITRA PERUSAHAAN - Ruliaty Ruliaty; Adb Salam; Saenab Saenab (Jurnal Ilmu Manajemen Profitability, 2017)
This research aims to determine the influence either together or partially between CSR (Corporate Social Responsibility) to corporate image in PT. Hadji Kalla Cabang Sultan Alaudin, Makassar area, that being measured from CSR  variables which is Profit, People, and Planet. Expectedly the information obtained from this research can be used by companies to increase CSR activities and quality of CSR programs so that more can enhance the company image in the  future. This study uses quantitative methods with explanatory research type with primary and secondary data. Population in this study is the customer PT. Hadji Kalla Cabang Sultan Alaudin, in Makassar and from the population the researcher take 100 adult people as research sample. As for the data analysis technique the researcher uses linear multiple regression and partial with SPSS 17  software. The result of this study found that variables within CSR  concept  which  is Profit (X1), People (X2), Planet (X3) simultaneously have a significant influence to the corporate image (Y). People (X2) became the most dominant variables that influence the corporate image with regression coefficient values  0,342.